Inducing incentive sensitization of exercise reinforcement among adults who do not regularly exercise—A randomized controlled trial - Flack, Kyle D. (PLoS One, 2019)
BACKGROUND: Increasing exercise reinforcement, or decreasing sedentary reinforcement, may reduce sedentary activity and promote habitual exercise. Repeated exposures to a reinforcer may increase its reinforcing value (i.e., incentive sensitization). It is not yet known whether incentive sensitization occurs for exercise or factors associated with incentive sensitization for exercise reinforcement. The purpose was to determine whether exercise exposures increase exercise reinforcement relative to a sedentary alternative and whether this sensitization of exercise reinforcement would alter physical or sedentary behavior. This work also determined whether exercise dose, intensity, and preference and tolerance for exercise intensity were associated with incentive sensitization of exercise. METHODS: 104 sedentary men and women were randomized to exercise training groups with 89 completing the study. Groups included exercise exposures of 150 (n = 35) or 300 kcal/session (n = 34), 3 sessions/week for 6 weeks, or a non-exercise control group (n = 35). Assessments for exercise and sedentary behavior reinforcement (primary dependent variables) and activity and tolerance for exercise intensity were performed at baseline (week 0), post training (week 6), and post washout (week 10). RESULTS: The control group reduced (P = 0.022) relative reinforcing value of exercise, such that the 150 kcal group had a greater relative reinforcing value of exercise after the exercise treatment 150 kcal: 0.69 ± 0.07 to 0.74 ± 0.07; 300 kcal: 0.72 ± 0.07 to 0.63 ± 0.08, control: 0.72 ± 0.07 to 0.57 ± 0.08 mean ± SE. Increases in tolerance for exercise intensity discomfort were associated with increases in relative reinforcing value of exercise. Sedentary behavior reinforcement decreased in both exercise groups (150 kcal: 5.4 ± 4.3 to 1.8 ± 1.3; 300 kcal: 5.4 ± 4.3 to 3.1 ± 2.4, P<0.05), but remained unchanged in the control group (5.1 ± 4.0 to 6.1 ± 4.9, P>0.05). Sedentary activity decreased baseline to post-training in the 300 kcal group (546.5 ± 10.7 to 503.8 ± 11.8 minutes, P<0.01). CONCLUSION: Small amounts of regular exercise may reduce the reinforcing value sedentary behavior. The process of incentive sensitization of exercise may include reducing the reinforcing value of competing sedentary activities. Developing tolerance to exercise discomfort of exercise may be critical to increasing exercise reinforcement.